Demonstration Method As A Strategy For Improving Democracy Culture In Citizenship Education Learning For Class VIII Students Of Smp Negeri 3 Kepenuhan Hulu - Suswanto Suswanto (Indonesian Journal of Basic Education, 2021)
The Demonstration Method as a Strategy for Increasing the Culture of Democracy in Citizenship Education Learning for Class VIII Students of SMP Negeri 3 Kecepatan Hulu, Kecepatan Hulu District, Rokan Hulu Regency. The demonstration method can improve the Culture of Democracy in Citizenship Education Learning for Class VIII Students of SMP Negeri 3 Kecepatan Hulu, Kecepatan Hulu District, Rokan Hulu Regency, there is an increase in learning in cycle II meeting II while the increase is very significant. In using this method the author really considers the time, the condition of the child, and the problems identified before conducting classroom action research, so that it is appropriate to take action, it is proven that there is an increase in successively from cycle I to meeting I to cycle II to meeting II, then it is proven in that cycle. This method can be implemented by identifying problems, formulating problems, planning, and implementing actions, and evaluating so that the results achieved can improve student achievement